Effect of Board of Directors Size, Board of Directors Characteristics, Ownership Structure, and Company Size on The Quality of Sustainability Reporting Disclosures - Dwi Setiawan; Agustin Fadjarenie; Lin Oktris (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to analyze the quality of Sustainability Reporting disclosures and test the factors that influence them. The quality of Sustainability Reporting disclosures is identified using content analysis techniques based on the GRI Standards. GRI Standards is the latest guideline launched by the Global Reporting Initiative which became effective in 2018 in Indonesia. Factors influencing the quality of Sustainability Reporting disclosures were tested using quantitative methods of multiple regression analysis. This study used 36 samples obtained through purposive sampling from infrastructure sector companies listed on the Indonesia Stock Exchange that disclosed sustainability reporting for the 2016-2021 period. The results showed that the quality of sustainability reporting in Indonesia is still relatively low at 17.41%. This implies that voluntary sustainability reporting disclosures make companies less motivated to make in-depth disclosures. The number and characteristics of the company's board of directors have a significant influence and the ownership structure and size of the company have a significant positive influence on the quality of sustainability reporting.